Ultrasound features of shoulder involvement in patients with ankylosing spondylitis: a case–control study - Ali Ou Alla, Sanae (BioMed Central, 2013)
BACKGROUND: During Ankylosing spondylitis (AS) courses, shoulder involvement is common. However, etiologies of shoulder pain in patients with AS remain to be defined. The aim of this study was to investigate the prevalence of ultrasound (US) abnormalities in shoulders of patients with ankylosing spondylitis (AS), and to determine predictive factors of ultrasound shoulder enthesitis. METHODS: 38 patients with AS were included with 38 age and sex-matched healthy controls. All patients fulfilled the modified New York criteria for ankylosing spondylitis. Clinical and demographical data were recorded. US examination of bilateral shoulders was performed by a musculoskeletal sonographer according to a defined protocol that included imaging of the insertions of supraspinatus, subscapularis and infraspinatus tendons, rotator cuff tendons, subacromial-subdeltoid bursa, acromioclavicular joint, and glenohumeral joint. RESULTS: The mean age of patients and controls was 36 years, each group of patients and controls comprised 22 men (57.9%) and 16 women (42.1%). Disease duration was 9.6 ± 7.2 years. Among 38 patients with AS, 21 had coxitis (55%) and 19 had previous or current shoulder pain (50%). AS shoulders presented significantly more ultrasound enthesitis than controls shoulders (43 shoulders (56.6%) versus 8 shoulders (10.5%) respectively). Involvement of rotator cuff tendons was significantly higher in patients with AS compared with control subjects (16/38 (42.1%) versus 6 (15.2%) respectively). However, involvement of gleno-humeral and acromio-clavicular joints was infrequent in both groups. In patients with AS, we found that the presence of coxitis was the only significant predictive factors of shoulder enthesitis (Odds Ratio (OR) = 9.4; Confidence interval (CI) 95% (1.10; 81.9), p = 0.04). CONCLUSIONS: Ultrasound abnormalities of shoulders are common in patients with AS, and the most frequent abnormalitie was enthesitis, which was associated with the presence of coxitis.